Efficient removal of Spartina alterniflora with low negative environmental impacts using imazapyr - Peng, He-Bo; Shi, Jianbin; Gan, Xiaojing; Zhang, Jing; Ma, Chao; Piersma, Theunis; Melville, David S. (Frontiers in Marine Science, 2022)
Invasion by smooth cordgrass (Spartina alterniflora Loisel) has greatly impacted the intertidal ecosystems of China. Worldwide, chemical control is the most widely used method to control Spartina species, but it has not been widely implemented along the Chinese coast due to concerns about the potential impacts of herbicide residues on the environment and organisms. Macrobenthos, both natural and cultured on intertidal mudflats, is an important seafood resource, so human food safety is a particular concern. Here we tested the effectiveness of imazapyr (an imidazolinone herbicide inhibiting the synthesis of branched-chain amino acids) in controlling S. alterniflora from August 2020 to June 2021 on the Jiangsu Coast, an area severely impacted by S. alterniflora. We used two different concentrations of the herbicide and monitored the density of S. alterniflora seedlings and flower spikelets, the effects of herbicide use on macrobenthos, and residues in organisms and the environment at different times post-application. Ten months after application, imazapyr had killed all plants and within 30 days it inhibited the two reproductive processes of germination and flowering; there were no significant differences between the two concentrations used. Imazapyr residues were detected in the environment for up to 14 days post-application, but at very low concentrations and exponentially decreased with time. No residues were found in any macrobenthos. Imazapyr use did not result in a reduction of macrobenthos density. We conclude that the herbicide imazapyr effectively removes S. alterniflora with little collateral damage to other organisms and the environment. However, in view of the relatively small scale of our trials and the great extent of S. alterniflora in many sites in China, we recommend that larger scale field trails be conducted to assess any potential adverse effects when imazapyr is used at a landscape level.